STUDI KOMPARATIF PROGRAM PENANGGULANGAN KEMISKINAN - Siti Nuraini (UNEJ e-Proceeding)
The government made policies to reduce poverty in a variety of programs. The purpose of this study was to determine the various poverty reduction programs in various countries with literature and comparative studies on poverty reduction programs in Indonesia. Program comparison is the impact of KALAHI-CIDDS in the Philippines, TASAF II in Tanzania, Nigeria and the Fadama II PNPM Mandiri and PKH in Indonesia. The results of this study indicate that there are good and bad of the various programs. Almost all programs have an impact on the decline of social capital in the community, the groups that make poor people more exclusive, and the lack of synergy between the program with local government policy.